Overtourism and Destination Authenticity Degradation: Testing Butler's Environmental Carrying Capacity Theory in Southeast Asian Mass Tourism Contexts - Solahuddin Nasution; Gustanto Gustanto; Koko Sujatmoko; Fretika Putri (Universitas Persada Indonesia YAI, 2026)
The phenomenon of overtourism has emerged as a central concern in global tourism studies, particularly in Southeast Asian destinations experiencing mass visitation surges in the post-pandemic era. This study examines destination authenticity degradation resulting from excessive tourism pressure through Butler's Tourist Area Life Cycle (TALC) and environmental carrying capacity frameworks, drawing on North Sumatra, Indonesia as its empirical context. Survey data were collected from 385 respondents across five destinations. Results indicate that three destinations have exceeded social and environmental carrying capacity thresholds, with authenticity degradation indices of 0.62–0.81. Policy implications include capacity-based visitor quotas and strengthened community governance.